Implementasi Algoritme SPECK dan SHA-3 Pada Database Rekam Medik - Hilman Adi Kartika; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Medical record data has to be protected because the data contains personal data about medical history owned by patients and doctors. However in recent years, many cases of attacks or hacking are found. This study aims to secure data records on the database. To secure the data by applying the SPECK algorithm is implemented to ensure data confidentiality and SHA-3 algorithm to ensure the integrity of the data. SPECK algorithm is applied to the name, address, description, and symptom fields of the patient table, while the SHA-3 algorithm is applied to the user table's password field. Tests conducted in this study are, validation test vector, encryption and decryption validation, performance time of encryption and decryption, system functionality, and non-functionality system. The results of the test shows that test vector, encryption and decryption test are valid. The execute time of encryption and decryption on average is 11,2 milisecond for encryption and 11,295 milisecond for decryption. Functionality of the system runs according to function, and non-functional systems can run well on various web-browsers such as Microsoft Edge, Mozilla Firefox, Google Chrome, and Opera.